2014
DOI: 10.1262/jrd.2014-062
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modification Agents Improve Genomic Methylation Reprogramming in Porcine Cloned Embryos

Abstract: Incomplete DNA methylation reprogramming in cloned embryos leads to low cloning efficiency. Our previous studies showed that the epigenetic modification agents 5-aza-2’-deoxycytidine (5-aza-dC) or trichostatin A (TSA) could enhance the developmental competence of porcine cloned embryos. Here, we investigated genomic methylation dynamics and specific gene expression levels during early embryonic development in pigs. In this study, our results showed that there was a typical wave of DNA demethylation and remethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 28 publications
(48 reference statements)
0
31
0
Order By: Relevance
“…Previous studies have shown that epigenetic modification agents could enhance cloning efficiency (Wang et al, 2011;Xu et al, 2013), and our previous results also demonstrate that 5-aza-dC can improve genomic methylation reprogramming and the development of cloned embryos (Huan et al, 2013(Huan et al, , 2014; however, the expression dynamics of genes involved in DNA methylation reprogramming and the relationship between the expression patterns of these genes and the developmental competence of porcine cloned embryos remain poorly studied. In this study, we first investigated the developmental progress of porcine early embryos, and then examined the stageby-stage transcripts of DNA methylation and demethylation related genes to elucidate the relationship between the developmental competence and expression patterns of DNA methylation reprogramming related genes (Dnmt1,Dnmt3a,Tet1,Tet2,Tet3,Aid,Tdg and Apex1) in porcine early embryos, thereby revealing the mechanism of DNA methylation reprogramming in early embryos.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…Previous studies have shown that epigenetic modification agents could enhance cloning efficiency (Wang et al, 2011;Xu et al, 2013), and our previous results also demonstrate that 5-aza-dC can improve genomic methylation reprogramming and the development of cloned embryos (Huan et al, 2013(Huan et al, , 2014; however, the expression dynamics of genes involved in DNA methylation reprogramming and the relationship between the expression patterns of these genes and the developmental competence of porcine cloned embryos remain poorly studied. In this study, we first investigated the developmental progress of porcine early embryos, and then examined the stageby-stage transcripts of DNA methylation and demethylation related genes to elucidate the relationship between the developmental competence and expression patterns of DNA methylation reprogramming related genes (Dnmt1,Dnmt3a,Tet1,Tet2,Tet3,Aid,Tdg and Apex1) in porcine early embryos, thereby revealing the mechanism of DNA methylation reprogramming in early embryos.…”
mentioning
confidence: 75%
“…However, in cloned embryos, continuous expression of Dnmt1s leads to aberrant demethylation (Chung et al, 2003;Yamanaka et al, 2011), and our results also showed that Dnmt1 transcripts were higher in porcine cloned embryos before the 8-cell stage. Additionally, Dnmt1 and Dnmt3a were not effectively activated after ZGA, possibly explaining the cause of incomplete DNA methylation reprogramming and low development of cloned embryos (Huan et al, 2014;Yamanaka et al, 2011). Furthermore, the expression patterns of Dnmt1 and Dnmt3a and the development of cloned embryos in IVF and NA embryos also reveal that effective silence and activation of Dnmts are essential for normal development of early embryos.…”
Section: The Developmental Competence Was Positively Correlated With mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the use of the artificial modifiers of epigenomically conditioned gene expression, gives rise to the inhibition of both chromatin condensation and transcriptional repression of the genomic DNA of cultured somatic cells that provide a source of donor nuclei for the reconstruction of enucleated oocytes and subsequent generation of cloned embryos (Saini et al, ; Su et al, ; Wang, Zhang, et al, ; Wang, Su, et al, ). On the one hand, those epigenetic modifiers represent not only the subclass of highly specific extrinsic HMT inhibitors (HMTi) such as G9A (H3K9) HMTi, whose pivotal member is diazepin‐quinazolin‐amine derivative termed BIX‐01294 (Cao et al, ; Huang et al, ), but also the subclass of ectopic non‐specific DNMT inhibitors, whose most important members are: (a) 5‐aza‐2′‐deoxycytidine (5‐aza‐dC) (Huan, Wang, et al, ; Huan, Wu, et al, ; Huan et al, , ; Ning et al, ); and (b) zebularine (a nucleoside analog of cytidine; Diao et al, ). On the other hand, they represent the subclass of ectopic non‐selective HDAC inhibitors (HDACi), whose main members are (a) TSA (Huan, Wang, et al, ; Huan, Wu, et al, ; Huan et al, ; Opiela et al, ; Samiec et al, ); (b) scriptaid (SCPT) (Liang, Zhao, Choi, Kim, & Cui, ; Xu et al, ; Zhang et al, ); (c) oxamflatin (Hou et al, ; Mao et al, ); (d) sodium butyrate (NaBu) (Kumar et al, ; Liu et al, ); (e) m ‐carboxycinnamic acid bis hydroxamide (CBHA) (Song et al, ); (f) panobinostat, also known as LBH589 (Jin et al, ); (g) abexinostat, also termed PCI‐24781 (Jin et al, ); (h) quisinostat, also called JNJ‐26481585 (Jin, Guo, et al, ); and (i) dacinostat, also named as LAQ824 (Jin, Lee, Taweechaipaisankul, Kim, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%